Está en la página 1de 10

Q

i

=

F(K, L)

q

Q

i

=

Q

f

=

F(

λ

K,

λ

L)

! " # $ !

1 d

+ dq

>

1

+

λ

1 d

+ dq

=

1

+

λ

1 d

+ dq

<

1

+

λ

dq

dq

dq

>

=

<

λ

d

λ

d

λ

d

dq

λ

d

dq

λ

d

dq

λ

d

>

=

<

1;

1;

1.

%

(

CT q Q

i

)

(

= c CT Q

i

)

&

' (

) " ! ' (

* $ * + !

(

CMg Q

) =

dCT Q

(

)

dQ

=

(1

+

dc

)

CT

i

CT

i

(1

+

dq

)

Q

i

Q

i

=

dc CT

i

dq

Q

i

+ +

 

dq

CMd Q

(

)

s =

 

=

dc

(

CMg Q

)

,

# - "

CT

C

λK

λK

K K

= p ⋅λ L + p ⋅λ K = λ⋅ (p ⋅ L + p
= p
⋅λ
L
+
p
⋅λ
K
= λ⋅
(p
L
+
p
K)
L
K
L
K
q⋅Q
q⋅Q
A A
Q Q
A A
CT
CT
CT
CT
CT CT
A A
B B
C C
L λL
L
λL

. ! . " - /

*

!

" )

& 0
& 0

c =

CT

B

CT

A

CT

C

CT

A

= λ

. + + !

1 + 2 3 4 5 +

+ # $ 3 4 3 ! 6 . $ 3 +!

. ! " ' ( ' (

. + ' ( " - " ' ( ' (

1

& $ 3 +

& " 7

dQ =

F

K

dK

+

F

L

dL

=

PMg

K

dK

+

PMg

L

dL

. ' (

dK

dL

=

=

*

dQ

=

(1

(1

+

+

λ

d

)

λ

d

)

PMg

K

K

K

L

L

=

K

dλ

+

=

L

K

λ

d

λ

d

PMg

L

L

dλ

) + 0 !

Q

+

dQ

 

dQ

 

(

PMg

K

K

+

PMg

L

L

)

λ

d

 

=

1

+

=

1

+

   
   
 

Q

 

Q

 

Q

 

dq

PMg

K

K

+

PMg

L

L

 

=

λ

d

Q

 

q =

2 & 4 5 ! "

* 0 ! 5 +

CT(Q) = min{p

L

L + p

K

K}

s.a.

F(K, L) Q = 0

.

8 ' ( ! ! 3 , " 0 ! 9 + +

LG =

LG

L

LG

K

p

=

=

LG =

µ

L

L

+

p

K

K

µ

0 µ

p

L

F

L

=

0 µ

p

K

F

K

=

0

Q

=

F(K, L)

(F(K, L)

Q)

0

p

L

=

µ

PMg

L

0

p

K

=

µ

PMg

K

$ 0 3 + 4 + 0 !

PMg

L

p

L

=

PMg

K

p

K

.

# ! ! 9 + + "

0 0 ! 0 5 + :

+ 5 +

µ =

p

L

PMg

L

=

p

K

PMg

K

= CMg

* +

 

dq

=

CMd = (

p

K

K

+

p

L

L

)

Q

Q

=

p

K

K

 

+

s =

dc

CMg

 

CMg

 

Q CMg

 

=

p

K

K

+

p

L

L

 

=

PMg

K

K

+

PMg

L

L

Q

p

K

   

p

L

 

Q

 

PMg

Q

K PMg

L

p

L

L

Q CMg

=

0 4 5 3 0 " *

dq = dq

dc

dλ

2 + $

' (

' ( ;

& + " $ " $ . $ ' + 5 ( 3" + + 3 4 5 + * + 3 4 5 + + 5 ! + + 5 +

3 # " $ ! " " ' 5 ( $ $ ' 0 $ ! <=> 9=>(